1997
DOI: 10.1080/03014469700004942
|View full text |Cite
|
Sign up to set email alerts
|

The validity of body mass index for the assessment of adiposity in children with disease states

Abstract: Recently published standards for body mass index (BMI) based on population studies of height and weight in healthy British children allow an easy but indirect assessment of adiposity in healthy children. However, assessment of adiposity based on standards derived from reference populations may not be appropriate for use in subjects with disease states associated with abnormalities of growth and body composition. This hypothesis was tested by comparison between BMI standard deviation scores (SDS) and more direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…Another limitation is the use of BMI as the only measure of obesity. BMI is reproducible and a simple way to assess obesity because it correlates with body fat in middle age people without major comorbidities, 27,28 but not in patients with coronary artery disease. We have recently reported that in patients with CAD, BMI fails to detect excess body fat, the true definition of obesity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Another limitation is the use of BMI as the only measure of obesity. BMI is reproducible and a simple way to assess obesity because it correlates with body fat in middle age people without major comorbidities, 27,28 but not in patients with coronary artery disease. We have recently reported that in patients with CAD, BMI fails to detect excess body fat, the true definition of obesity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Like many useful screening tools, however, its value becomes less clear when looking at extremes and severe disease states. Its validity as a measure of body composition has been questioned in adult eating disorder patients (Hannan et al, 1995), and in paediatric patients in general (Warner et al, 1997). The limitations of BMI or equivalent ratio measures of body composition (eg weight-for-height or BMI standard deviation scores, s.d.s) lie in their poor capacity to discriminate underweight from inadequate body fat.…”
Section: Introductionmentioning
confidence: 99%
“…10 ± 13 There is also a concern that sensitivityaspeci®city of the commonly used obesity de®nitions might differ between the sexes, 10,13 though not all studies have reported this. 11,12 If the sensitivity of BMI, when used to screen for obesity, differed signi®cantly between the sexes, then different screening toolsaobesity de®-nitions would have to be used for boys and girls. A further disadvantage of the BMI is that it has limitations as a means of monitoring secular trends in childhood obesity: changes in fat-free (lean body) mass cannot always be readily distinguished from changes in fat mass since BMI is a proxy for both.…”
Section: Introductionmentioning
confidence: 99%